2022
DOI: 10.1101/2022.08.29.505770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thinking outside the CaaX-box: an unusual reversible prenylation on ALDH9A1

Abstract: Protein lipidation is a post-translational modification that confers hydrophobicity on protein substrates to control their cellular localization, mediate protein trafficking, and regulate protein function. In particular, protein prenylation is a C-terminal modification on proteins bearing canonical prenylation motifs catalyzed by prenyltransferases. Such types of proteins have been of interest owing to their potential association with various diseases. Chemical proteomic approaches have been pursued over the l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Those proteins are 4-trimethylaminobutyraldehyde dehydrogenase (Aldh9A1), Ras-related protein Ral-A (Rala), Synaptobrevin homologue Ykt6 (Ykt6), Ubiquitin carboxyl-terminal hydrolase isozyme L1 (Uchl1), Cell division control protein 42 homologue (Cdc42), Ras-related protein Rap-1b;1a,(Rab1b;Rap1a), 2,3-cyclic-nucleotide 3-phosphodiesterase (Cnp), Rab10, Rab11a;b, Rab18, Rab1a;b, Rab2a;b, Rab35, Rab3a, and Rab6a;b (Figure C). While ALDH9A1 is listed here as a farnesylated protein, the identity of the isoprenoid on this protein and the mechanism of its prenylation have not been unambiguously established . Ranking of the enriched proteins by either their average fold change or π-score revealed that Rab18 was the top ranked protein on both lists (SI Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those proteins are 4-trimethylaminobutyraldehyde dehydrogenase (Aldh9A1), Ras-related protein Ral-A (Rala), Synaptobrevin homologue Ykt6 (Ykt6), Ubiquitin carboxyl-terminal hydrolase isozyme L1 (Uchl1), Cell division control protein 42 homologue (Cdc42), Ras-related protein Rap-1b;1a,(Rab1b;Rap1a), 2,3-cyclic-nucleotide 3-phosphodiesterase (Cnp), Rab10, Rab11a;b, Rab18, Rab1a;b, Rab2a;b, Rab35, Rab3a, and Rab6a;b (Figure C). While ALDH9A1 is listed here as a farnesylated protein, the identity of the isoprenoid on this protein and the mechanism of its prenylation have not been unambiguously established . Ranking of the enriched proteins by either their average fold change or π-score revealed that Rab18 was the top ranked protein on both lists (SI Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…While ALDH9A1 is listed here as a farnesylated protein, the identity of the isoprenoid on this protein and the mechanism of its prenylation have not been unambiguously established. 42 Ranking of the enriched proteins by either their average fold change or π-score revealed that Rab18 was the top ranked protein on both lists (SI Figure 4). 43 Many of these proteins have previously been implicated as key players in the processing and regulation of Aβ peptide, APP, or tau proteins as highlighted in SI Table 1.…”
Section: Proteomic Analysis Identified Significantly Enriched Prenyla...mentioning
confidence: 99%